2020
DOI: 10.1136/archdischild-2020-319767
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of retinopathy of prematurity in Germany: evaluation of current screening criteria

Abstract: ObjectiveTo evaluate current screening criteria for retinopathy of prematurity (ROP) by investigating the incidence of ROP requiring treatment in infants with gestational age (GA) ≥30 weeks or postmenstrual age (PMA) <32 weeks in Germany.MethodsThree patient databases were analysed, that is, the German Quality Assurance Procedure in Neonatology (years 2011–2017; n=52 461 infants screened for ROP, 1505 infants treated for ROP), the German Retina.net ROP Registry (years 2011–2018; n=281 treated infants) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
1
14
0
8
Order By: Relevance
“…Larsen et al have suggested that modifying the GA threshold to < 30 weeks in the screening guidelines would lower the burden of screening examinations with acceptable impact on the sensitivity of screening programs [ 3 ]. Indeed, applying this modified GA limit of < 30 weeks would not have altered the screening sensitivity for predicting treatment-required ROP in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Larsen et al have suggested that modifying the GA threshold to < 30 weeks in the screening guidelines would lower the burden of screening examinations with acceptable impact on the sensitivity of screening programs [ 3 ]. Indeed, applying this modified GA limit of < 30 weeks would not have altered the screening sensitivity for predicting treatment-required ROP in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While in some high-income countries the sensitivity of G-ROP criteria to predict type 1 ROP in validation studies was 100%, [ 11 , 12 ] lower sensitivity (91.9%) has been suggested in less mature healthcare systems such as Turkey [ 13 ]. These differences may have resulted from different neonatal care practices and different characteristics of the premature population in low- and middle-income countries [ 15 ].In Switzerland and Germany, less than 1% of infants with GA > 30 weeks developed treatment requiring ROP, [ 3 , 17 ] but in Mexico, over one-third of preterm infants with GA > 32 weeks may develop ROP type 1 [ 18 ]. Moreover, careful attention is needed in countries with less tightly controlled use of oxygen supplementation, as postnatal weight gain is not a reliable predictive factor of ROP when an infant is treated with excessive oxygen supplementation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the incidence of ROP screening both in 2019 and 2020 was 6.7%, lower than previous reports [1,14], which may be due to the reason that the infants without systematic diseases in outpatient clinic had relatively high gestational ages and birth weights. It was well-known that low gestational age and birth weight were still the major risk factors for ROP [15,16]. In North America, new ROP screening criteria [17,18] include gestational age < 28 weeks and weight gain at 40 days after birth, which had higher sensitivity and specificity for ROP type 1 than current criteria, and lead to 30% less screening population [17].…”
Section: Discussionmentioning
confidence: 99%